Towards the democratization of the future: The struggle for social recognition and economic success of a West African association of working children and youth. (May 2019) - Fuchs, Sarah
The African Movement of Working Children and Youth aims to empower and support young people, who otherwise would be excluded from educational and socioeconomic chances, to 'prepare their future'. In so doing, they re-interpret and re-combine transnational and local frames of reference in order to legitimize and materialize their ideas. I conceptualize this commitment as promoting a democratization of the future because they broaden the meaning of the (good) future as well as the means of access to it.